Criminological typology of radical criminals among sentenced to imprisonment (Law and Safety, 2023)
The article is devoted to the study of radical criminals among those sentenced to imprisonment. The purpose of the article is to provide a criminological typological characteristic of criminal radicals among those sentenced to imprisonment. The following tasks have been solved to achieve this goal: 1) to define the typological criteria for the division of criminal radicals among those sentenced to imprisonment; 2) to identify the relevant criminological types according to the criteria; 3) to identify and describe the signs of criminological types of criminal radicals among those sentenced to imprisonment.It has been proposed that 7 typological personal criteria should be used in scientific use and practical criminal prevention activities: by nature, by the direction of criminal and radical actions, by the contextual element of personal radicalisation, by the source of radical attitude, by the peculiarities of the radical’s predicate state, by the existential content of criminal and radical behaviour, and by the dominant social and role feature. According to them, 22 criminological types (including subtypes) of criminal radicals among convicts were identified. The author describes the key criminologically significant features of each type. The integrated typological characteristics of radical criminals among convicts give grounds to note that most of them can be correlated with an initiative, aggressive, rational-conformist, collectivist radical of an inclusive type.Both the initial diagnostic work of the relevant units and officials of the quarantine, diagnostic and distribution sectors of correctional colonies, as well as the further work of social and psychological work inspectors, should be aimed at identifying and recording these features. It has been argued that this information should also be taken into account when organising and carrying out operational work among prisoners in order to block the development of motivations for radical actions in a timely manner and to stop the tendencies of radicalisation among prisoners.It has been noted that the proposed typology of criminal radicals in penitentiary institutions is not closed, exhaustive, and can be supplemented with other criteria and types depending on the researcher's target setting and a specific applied request in the field of prevention of criminal radical manifestations in penitentiary institutions.
Keywords: criminal radicalism; imprisonment; penitentiary institutions; radical personality; typology.